Immediate implant loading with fixed dental restorations: An animal model study - Špadijer-Gostović Aleksandra; Todorović Aleksandar; Lazić Vojkan; Todorović Ana; Milinković Iva; Leković Vojislav (Vojnosanitetski Pregled)
Background/Aim. Immediate loading is considered to be the most innovative technique in contemporary implant dentistry. Recent clinical and experimental findings have demonstrated that only implants with high primary stability can be subjected to immediate loading protocol with predictable results. It is generally accepted that the most important prerequsite for successful osseointegration is achievement and maintenance of implant stability. The aim of this in vivo study was to investigate the possibility for successful application of immediate loading protocol in implant systems with different surface properties. Methods. In the experimental study 2 mongrel dogs were edentulated bilaterally in the mandibular and maxillary premolar areas. After 3 months implants were placed in a pattern 4 different commercially available implants per quadrant (n = 32): Mk III TiUnite (Nobel Biocare, Sweden), ITI TPS (Straumann, Switzerland), 3IOsseotite (Implant Innovation, USA) and XiVE Cell-Plus (Friadent, Germany). Implants were subjected to immediate loading with 4 unit gold cast bridges, 2 days post implantation. The assessment of implant stability and immediate loading possibilities were done by performing Resonance frequency analysis (RFA). Results. After a 6- month loading period all bridges were in function and all implants occurred well osseointegrated. When summarizing the Implant Stability Quotient (ISQ) values, it was noted that resonance frequency was significantly higher for mandibular implants. The results of this experimental setting showed that all evaluated surfaces achieved good implant stability. Increase of ISQ values was found for all implants in the mandible and partially decrease of ISQ values for maxillary implants after 6 months of functional loading with 4 unit bridges. Conclusions. Investigated endooseal implants did not show different degree of osseointegration, because there was not statisticaly significant difference among observed parameters (ISQh i ISQp) between implant systems.